Dynamically Programmed Switchable DNA Hydrogels Based on a DNA Circuit Mechanism. Issue 15 (12th March 2019) - Oishi, Motoi; Nakatani, Kazuki
Abstract: Biological stimuli‐responsive DNA hydrogels have attracted much attention in the field of medical engineering owing to their unique phase transitions from gel to sol through cleavage of DNA cross‐linking points in response to specific biomolecular inputs. In this paper, a new class of biological stimuli‐responsive DNA hydrogels with a dynamically programmed DNA system that relies on a DNA circuit system through cascading toehold‐mediated DNA displacement reactions is constructed, allowing the catalytic cleavage of cross‐linking points and main chains in response to an appropriate DNA input. The dynamically programmed DNA hydrogels exhibit a significant sharp phase transition from gel to sol in comparison to another DNA hydrogel showing noncatalytic cleavage of cross‐linking points due to synchronization of the catalytic cleavage of cross‐linking points and the main chains. Further, the sol–gel phase transitions of the DNA hydrogels in response to the DNA input are easily tunable by changing the cross‐linking density. Additionally, with a structure‐switching aptamer, DNA hydrogels encapsulating PEGylated gold nanoparticles can be used as enzyme‐free signal amplifiers for the colorimetric detection of adenosine 5′‐triphosphate (ATP); this detection system provides simplicity and higher sensitivity (limit of detection: 5.6 × 10 −6 m at 30 min) compared to other DNA hydrogel‐based ATP detection systems. Abstract : A new class of switchable DNA hydrogels with a dynamically programmed DNA system is devised based on a DNA circuit system through cascading toehold‐mediated DNA displacement reactions. The DNA hydrogels exhibit a significant sharp phase transition due to synchronization of the catalytic cleavage of cross‐linking points and the main chains in response to an appropriate input.